Fluid mechanics - Streeter, Victor Lyle; Wylie, E. Benjamin (New York : McGraw Hill Education, 1983)
A comprehensive textbook on the fundamentals and applications of fluid mechanics.
Fundamentals of fluid mechanics -- Applications of fluid mechanics
Includes index.
Keywords: FLUID MECHANICS